Bridging Technology and Pedagogy: The Impact of AI-Generated Word Cards on Students’ Reading Comprehension - Ruslina, Isma; Settiawan, Dodi (State Islamic University of Sultan Syarif Kasim Riau, 2024)
This study investigates the effectiveness of AI-generated word cards as an instructional tool to improve reading comprehension among ninth-grade EFL students in Indonesia. Employing a quasi-experimental design, the research involved 68 participants divided into an experimental group, which received instruction using AI-generated word cards, and a control group, which followed traditional teaching methods. The word cards were designed to align with the school curriculum, incorporating vocabulary and phrases relevant to the students' learning objectives. Data was collected through pre-test and post-test assessments and analyzed using the Independent Samples t-test to determine the intervention's statistical significance. The results revealed a substantial improvement in the experimental group's reading comprehension scores compared to the control group, with the effect size indicating a significant impact. The findings highlight the potential of AI-driven tools to enhance vocabulary acquisition and comprehension skills, addressing gaps in traditional instruction. This study contributes to the growing body of evidence supporting the integration of AI in EFL pedagogy, offering innovative strategies to bridge technology and education effectively.